Influence of Protective Media Composition and Storage Temperature on Frozen-Dried Saccharomyces cerevisiae Yeast Survival - Tsutsayeva, A. A.; Balyberdina, L. M.; Pavlenko, N. V. (Problems of Cryobiology and Cryomedicine, 2004)
The effect of thiourea, as an antioxidant in cryoprotective medium under freeze-drying, on the baker’s yeast frozen-dried culture storage, was studied. Thiourea statistically and significantly increases their storage term in a viable state under 4° and -10°C. A number of viable cells and their properties remained unchanged under -25° and -75°C.